Pengaruh Locus Of Control Dan Lingkungan Kerja Terhadap Kinerja Guru SMKN 4 Klaten Dengan Kepuasan Kerja Sebagai Variabel Intervening - Utomo, Agus; Hesti, Hesti (-)
The purpose of this study is to examine the effect of locus of control, work environment and job satisfaction on the performance of teachers at SMK 4 Klaten. Hypotheses that have been formulated in this study were: significant effect of locus of control and the work environment directly and indirectly through job satisfication on the performance of teachers at SMK 4 Klaten.Keywords: locus of control, work environment, satisfaction, performance